2015
DOI: 10.1002/ceat.201400320
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Alkalinity on the Efficiency and Catalyst Behavior of Photo‐Assisted Processes

Abstract: The influence of carbonates on TiO 2 photocatalysis and the photo-Fenton process using Fe 0 as catalyst is unraveled. The aggregation behavior of each catalyst was monitored under different reaction conditions in order to assess the effect of carbonates on their performance. Carbonates drastically reduced the efficiency of photocatalysis because of aggregation of the TiO 2 catalyst, which led to the reduction of adsorbed pollutants. The addition of carbonates to the photo-Fenton process did not produce this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Similar results were reported by Jamil et al (2011). Moreover, Merayo et al (2016) reported good efficiency for the heterogeneous photo-Fenton treatment of lignin using zero valent iron microspheres as catalyst instead of ferrous iron. Lucas et al (2012) and Fernandes et al (2014) reported effective treatment of pulp mill wastewater with a solar-Fenton process.…”
Section: Fenton and Photo-fenton Processessupporting
confidence: 85%
See 2 more Smart Citations
“…Similar results were reported by Jamil et al (2011). Moreover, Merayo et al (2016) reported good efficiency for the heterogeneous photo-Fenton treatment of lignin using zero valent iron microspheres as catalyst instead of ferrous iron. Lucas et al (2012) and Fernandes et al (2014) reported effective treatment of pulp mill wastewater with a solar-Fenton process.…”
Section: Fenton and Photo-fenton Processessupporting
confidence: 85%
“…Other factors include the more frequent availability of ozone treatments for bleaching stages in paper mills, as well as some disadvantages of Fenton processes application, such as the production of iron sludge and the requirement of acidic conditions for optimal performance. These drawbacks may be overcome by using heterogeneous catalysts or by applying these treatments at neutral pH (Merayo et al 2016;Hermosilla et al 2012a). Beltrán-Heredia et al (2001) tested the use of sequential treatments with Fenton reagants and ozone.…”
Section: Fenton and Photo-fenton Processesmentioning
confidence: 99%
See 1 more Smart Citation
“… , This possibility would lead to an overall higher concentration of free carbonate anions in the amaranth solutions containing MMC when compared with an amaranth solution containing crystalline MgCO 3 . The radical scavenging properties of CO 3 2– and its affinity to hydroxyl radicals have been well documented, and this could be an explanation for the lack of catalytic activity from TiO 2 and ZnO in the presence of MMC (in mixture or as a support) in aqueous environments.…”
Section: Resultsmentioning
confidence: 99%